Influence of Childhood Psychological Maltreatment on Peer Attachment Among Chinese Adolescents: The Mediation Effects of Emotion Regulation Strategies - Yu, Tengxu (Journal of interpersonal violence, 2023)
The formation of peer attachment is vitally important for the mental health of adolescents. Additionally, converging evidences show that childhood emotional trauma leads to poor peer attachment during adolescence. However, little is known about the underlying mechanism accounting for the link between early emotional trauma and adolescent peer attachment. Therefore, the present study is intended to examine the relationship between childhood psychological maltreatment (CPM) and peer attachment among Chinese adolescents and reveal its underlying mechanism. In total, we collected data from 670 adolescents (36.5% males and 63.5% females, Mage = 16.44 years, SD = 0.78) attending two Chinese high schools. These participants completed measurement scales for CPM (emotional abuse and neglect), peer attachment, and emotion regulation strategies, including cognitive reappraisal (CR) and expressive suppression (ES). The multiple mediation models showed that emotional neglect negatively predicted adolescent peer attachment but that emotional abuse did not. Furthermore, the two emotion regulation strategies, CR and ES, completely mediated the relationship between emotional abuse and peer attachment and partially mediated the relationship between emotional neglect and peer attachment. These findings extend the existing studies on adolescent peer attachment and elucidate how childhood emotional trauma negatively influences adolescent peer attachment. In addition, the present results provide implications for improving the peer attachment of adolescents. On one hand, appropriate family intervention should be implemented to reduce CPM. On the other hand, schools can focus on improving the peer attachment of adolescents by enhancing their emotion regulation. Specifically, adolescents should be taught how to use adaptive strategies, such as CR, to regulate negative emotions.